Medical tourist’s perception in selecting their destination: a global perspective - Sarwar, Abdullah Al-Mamun; Abd. Manaf, Noor Hazilah; Omar, Azura (Iranian Journal of Public Health, 2012)
Background: The need for better healthcare has grown significantly in recent years. In addition, the rising healthcare costs in the U.S. and in many European countries have forced many patients to seek medical treatment abroad, which has created the demand for medical tourism. With little yet known as to the perception of a medical tourist’s destination selection, this study aims to explore medical tourist’s perception in selecting their destination while going for medical treatment.